1998
DOI: 10.1038/bjc.1998.19
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognostic factors of early ovarian cancer

Abstract: Summary Survival and prognostic factors were analysed in 150 patients with histologically confirmed epithelial ovarian cancer stage IA-IIA. The relapse-free and overall survival rates were, respectively, 81 % and 88% after 3 and 74% and 84% after 5 al, 1996). Other studies, however, did not confirm these indications (Dembo et al, 1986(Dembo et al, , 1990 Kaplan-Meier and compared using the log-rank test. The Cox model (Cox, 1972) was fitted to the data after graphical check of proportional hazards assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
4
2
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 8 publications
4
4
2
1
Order By: Relevance
“…This rate was approximately similar to the survival of patients treated radically reported in the literature. 16,21 However, the survival of patients with Grade 2 early stage diseases was quite different from survival reported in the literature. In the literature, survival of patients with this type of tumor varies from 77% to 94% whereas in our study the DFS in patients with Stage IA Grade 2 tumor was only 68%.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…This rate was approximately similar to the survival of patients treated radically reported in the literature. 16,21 However, the survival of patients with Grade 2 early stage diseases was quite different from survival reported in the literature. In the literature, survival of patients with this type of tumor varies from 77% to 94% whereas in our study the DFS in patients with Stage IA Grade 2 tumor was only 68%.…”
Section: Discussioncontrasting
confidence: 45%
“…Patients with clear cell tumors seem to have a worse survival rate than those with serous, mucinous, and endometrioid tumors. 16,19 Therefore, we think that conservative management could be discussed for patients with serous, mucinous, or endometrioid tumors but should not be performed in patients with more aggressive tumors such as clear cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have also been confirmed by other, smaller studies. 11,14,16,30,[36][37][38][39][40][41][42][43][44] In this current analysis, malignant cytology was an independent prognostic factor for increased risk of recurrence and poorer survival. Early studies have demonstrated that patients with positive washing have a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with clear cell EOC have poorer outcomes than patients with other histologic types of EOC, regardless of tumor stage [50,51]. Because of the rarity of clear cell EOC, the safety of fertility-sparing surgery is difficult to determine in patients with early-stage clear cell EOC.…”
Section: Text Of Reviewmentioning
confidence: 99%